2009
DOI: 10.1074/mcp.m800313-mcp200
|View full text |Cite
|
Sign up to set email alerts
|

Mining the Ovarian Cancer Ascites Proteome for Potential Ovarian Cancer Biomarkers

Abstract: Current ovarian cancer biomarkers are inadequate because of their relatively low diagnostic sensitivity and specificity. There is a need to discover and validate novel ovarian cancer biomarkers that are suitable for early diagnosis, monitoring, and prediction of therapeutic response. We performed an in-depth proteomics analysis of ovarian cancer ascites fluid. Size exclusion chromatography and ultrafiltration were used to remove high abundance proteins with molecular mass >30 kDa. After trypsin digestion, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
111
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 114 publications
(115 citation statements)
references
References 53 publications
2
111
0
Order By: Relevance
“…The concentration of soluble factors is usually much higher in ascites compared to serum, which increases the likelihood of detecting low abundance proteins [24,57]. In that context, proteomic/peptidomic proiling of ascites has been employed for biomarker discovery [59][60][61]. Diferent experimental approaches were used leading to the identiication of various sets of biomarkers all of which requiring further validation to determine their true potential.…”
Section: Cell-free Ascites: Biomarkers and Eoc Progressionmentioning
confidence: 99%
“…The concentration of soluble factors is usually much higher in ascites compared to serum, which increases the likelihood of detecting low abundance proteins [24,57]. In that context, proteomic/peptidomic proiling of ascites has been employed for biomarker discovery [59][60][61]. Diferent experimental approaches were used leading to the identiication of various sets of biomarkers all of which requiring further validation to determine their true potential.…”
Section: Cell-free Ascites: Biomarkers and Eoc Progressionmentioning
confidence: 99%
“…This is due to the fact that some well-known and previously studied proteins in the context of ovarian cancer were also identified ( Table 2 ). These include the classical ovarian cancer biomarker CA125 and others such as mesothelin, WFDC2 (HE4), α 2-macroglobulin, cathepsin D, and clusterin, which have shown promise as ovarian cancer biomarkers [ 17 ]. The glycosylation status of a number of these proteins has been studied in various contexts and some were reported to be sialylated ( Table 2 ) lending further support to our methodology.…”
Section: Discussionmentioning
confidence: 66%
“…Kuk et al [3] stated that nidogen-2 was elevated in the serum of patients with ovarian carcinoma, compared to patients with benign gynecological diseases and normal controls. Statistical analysis demonstrated that nidogen-2 has a potential diagnostic value.…”
Section: Discussionmentioning
confidence: 99%
“…Based on ovarian cancer prevalence, which is 1.3% [12], the expected sensitivity of nidogen-2 based on previous study is 55% and the expected specificity is 90% [3]; CI is 95% and the desired precision in this study will be 0.05 for specificity; accordingly, the sample size was calculated as 144 cases.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation